Hybrid system of nickel–cobalt hydroxide on carbonised natural cellulose materials for supercapacitors - Jiang, L; Shanmuganathan, S; Nelson, GW; Han, SO; Kim, H; Sim, I; Foord, JS (Springer Berlin Heidelberg, 2017)
Advanced carbon materials formed from abundant biomass are an exciting and promising class for energy devices due to the clear advantages of low cost, sustainability and good physical and electrochemical properties. However, these materials typically do not compete well with their metal functionalised counterparts. In this work, we demonstrate that xCo(OH) 2 –(1−x)Ni(OH) 2 with various Ni:Co ratios can be deposited onto biomass-derived carbon to make a hybrid inorganic-carbon electrode with tuneable physical features and electrochemical performance. These features were tuned by adjusting the Ni:Co ratio within precursor solutions. The electrodes had shown a capacitance ranging from 780.7 to 2041 F g −1 , which is very close to the theoretical value for Ni(OH) 2 (2365 F g −1 ). A hypothesis is presented to help explain this performance for a modified, biomass-derived carbon electrode.